Functions of City Parks on Public Life - Tanchangya, Aiendrela; Saika, Ummeh (The Jahangirnagar Review, 2024)
Residents of the city can benefit in a variety of ways from the presence of city parks, including their health, social lives, recreational opportunities, and the environment. In recent years, a growing body of research has supported the idea that better understanding the preferences of urban residents should be successful in the management of urban green space. The purpose of this study is to comprehend the purpose, motives, and attitude towards urban parks in various socio-demographic assortments, as well as the variety of preferences with regard to the park quality. A poll using questionnaires was carried out in a municipal park that was chosen at random in Chattogram, which is Bangladesh's one of the most populous and important commercial metropolis. According to the findings of the study, there is an interesting public perspective about the use of city parks, which depends on a mix of preferences about aesthetics and benefits regarding the environment. The conclusion demonstrates that many socio-demographic criteria, such as gender, age groups, educational level, and economic status, all play a role in determining whether or not people attend parks. It also reveals that the vast majority of respondents go to parks in order to obtain "social benefits" (21.66%), as well as "psychological and health benefits" (55.83%). In addition, it was shown that opinions aligned with seven criteria to determine the quality of a park. These criteria are the presence of a water body, park security, sanitary facility, historical significance, children's playground, and noise level. Overall, this study will be beneficial in the assessment of park users' motives and their attitudes, which is fundamentally required to manage city park functions in a multi-dimensional construct. This assessment is crucial to ensuring that city parks continue to serve their intended purposes.